2015
DOI: 10.1016/j.clae.2015.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Dry eye specific quality of life in veterans using glaucoma drops

Abstract: Purpose To evaluate the frequency of ocular surface symptoms and their potential impact on dry eye specific quality of life (QoL) in patients using versus not using glaucoma medications. Material and methods The study was a single-center, cross-sectional survey of patients seen at the Miami Veterans Affairs (VA) ophthalmology and optometry clinics from June to August, 2010. Patients were invited to complete the Dry Eye Questionnaire 5 (DEQ5) and the Impact of Dry Eye on Everyday Life (IDEEL) at their visit. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
26
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 45 publications
(57 reference statements)
3
26
0
1
Order By: Relevance
“…While some authors report no significant differences compared with control subjects not receiving antiglaucoma eyedrops (20,(25)(26)(27) several others note a difference in OSD prevalence (18,19,22,24), as observed here. Although the latter rates were similar to those of the present study, the slightly higher reported rates could be attributed to differences in demographics, such as ethnicity or sex (black individuals and women show a higher prevalence of OSD (21,36)), treatment duration (23), previous ocular conditions or surgery, and glaucoma severity (18,19). The population examined here comprised Caucasian subjects who had not undergone prior eye surgery besides cataract (>6 months before recruitment), showed a balanced sex distribution, and lacked individuals with advanced or terminal glaucoma stages.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…While some authors report no significant differences compared with control subjects not receiving antiglaucoma eyedrops (20,(25)(26)(27) several others note a difference in OSD prevalence (18,19,22,24), as observed here. Although the latter rates were similar to those of the present study, the slightly higher reported rates could be attributed to differences in demographics, such as ethnicity or sex (black individuals and women show a higher prevalence of OSD (21,36)), treatment duration (23), previous ocular conditions or surgery, and glaucoma severity (18,19). The population examined here comprised Caucasian subjects who had not undergone prior eye surgery besides cataract (>6 months before recruitment), showed a balanced sex distribution, and lacked individuals with advanced or terminal glaucoma stages.…”
Section: Discussionsupporting
confidence: 87%
“…This total score was recorded for each participant. The impact of dry eye was then assessed categorically as normal (scores of 0-12), mild (scores of [13][14][15][16][17][18][19][20][21][22], moderate (scores of [23][24][25][26][27][28][29][30][31][32], or severe (scores of 33-100), as previously described (17,24).…”
Section: Ocular Surface Disease Indexmentioning
confidence: 99%
“…All domains offer a score, which goes from zero (representing total impairment) to 100 (representing no impairment) (20) .…”
Section: Consequentsmentioning
confidence: 99%
“…Es gibt bislang wenige Untersuchungen zur direkten Auswirkung der Tropftherapie bei Glaukompatienten. Gesichert ist der Zu- sammenhang zwischen der Anzahl an Glaukommedikation mit Beschwerden durch trockenes Auge und emotionaler Lebensqualität [30]. Außerdem konnte eine gute Prädiktion der Oberflächenstörung bei Glaukompatienten durch den GQL-15-Score getroffen werden [31].…”
Section: Tropftherapie Und Lebensqualitätunclassified